Synchronisation of output voltage waveforms in phase synchronous inverter with LCL filter for smart grid systems - Rahman, Tawfikur; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Azam, S. M. Kayser (UPM Press, Universiti Putra Malaysia, 2017)
Nowadays, smart grid system is widely used for energy supply system because it is simple, available, less costly, highly efficient and environmentally friendly. Conventionally, inverter techniques are utilized to convert input DC into output AC with the same frequency and phase. These techniques introduce some problems with higher harmonic distortion, phase synchronization, lower quality of waveform and long distance. A three phase synchronous inverters (PSI) have been applied to zero crossing with pulse width modulation (PWM) controller, LCL filter, three phase RLC load, three phase Star-Delta transformer, 5km feeder with 2 MW load. Zero crossing with pulse generator is used to generate the pulse signal for synchronization between inverter and grid system. However, LCL filters have been employed to reduce the system noise. The proposed technique has been used for a balanced three phase load (10 kVAR ) and an input DC voltage of ± 250V. In order to increase the inverter output voltage and current with the fundamental frequency (50Hz) a three phase transformer (100kVA/260V/25kV) has been considered. The system results in conversion efficiency at 97.96% and phase synchronous error for each phase as 4.5 degrees.